Organoruthenium 9E1 and APL Altered Collagen II263-272 Peptide as Therapy for Autoimmune Diseases - Safruddin, Khairu Zein; Martdana, Ardhin; Seipalla, Fenska; Sosanta, Tirza (PT. Riset Press International, 2023)
Therapy for autoimmune diseases such as rheumatoid arthritis and multiple sclerosis (MS) is currently available in symptom management, pain-relieving, and mitigation of disease. Currently, prescribed drugs for patients with the disease work in specific mechanisms, regardless of failure to determine the most effective medication. We use a literature review to highlight two newly examined substances: organoruthenium 9E1 and APL altered collagen II263-272 peptide, and elaborate substances mentioned above' potential to be used in rheumatoid arthritis and MS therapy. Several studies show positive effects from 9E1 and altered CII263-272 peptides on experimented mice. Altered CII263-272 peptide can elicit Th cells to produce neurotrophic factors, decrease the body amount of pro-inflammatory T cells, increase the body amount of anti-inflammatory T cells, and alleviate collagen-induced arthritis symptoms. Meanwhile, 9E1 can inhibit Mst1 kinase effectively (IC50=45nM), giving consequences of decreasing Th1 cells' cytokines, increasing Th2 cells' cytokines, decreasing body amount's IgG1 and IgG2a, slowing down EAE and collagen-induced arthritis' manifestation, increasing IL-10 and IL-4-producing T cells. Organoruthenium and altered CII263-272 peptide possess positive and multiple effects as therapies for EAE and collagen-induced arthritis, hence potential to be prescribed to patients with rheumatoid arthritis and MS. This literature review suggests further research concerning 9E1 and altered CII263-272 peptide usage in the community to examine their effectivity, side effects, and suitable dose.